Of Times, Religions, and Revolutions: One Unites into Two - Reihanzadeh, Arsalan (Filozofski vestnik, 2023)
Starting from the impact of biblical teachings on Islam, the first part of this article attempts to show the divergent paths that Christianity and Islam have taken when confronted with the three dimensions of time (chronos, kairos, krisis). The article aims to elucidate the distinct onto-theologies of the two religious discourses by analysing various examples that illustrate this divergence. Consequently, the onto-theology of Islam can be encapsulated as “One unites in two,” in contrast to the onto-theology of Christianity, which can be formulated as “One divides into two.” In the second part of the article, one of the political implications of the onto-theology of “One united in two” is examined in depth in a socio-political context, showing how the conceptualisation of such a context can only be done adequately if its onto-theological dimension is taken into account.